2020
DOI: 10.1007/s11764-020-00941-4
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation versus exercise for improved quality of life in lymphoma survivors—a randomised controlled trial

Abstract: Purpose Lymphoma survivors experience persisting needs as a consequence of disease and treatment, which have an impact on quality of life (QoL). There is evidence supporting the use of relaxation and exercise to improve QoL, but there is no agreement on which is more beneficial. This study aims to compare a relaxation intervention versus an exercise intervention to determine which has a greater impact on QoL post-chemotherapy. Methods Eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 62 publications
2
10
0
7
Order By: Relevance
“…Meanwhile, some nurses still believe that cancer related-fatigue is a normal response that experienced by women after chemotherapy, so it does not require intervention (Sanada et al 2017). Other than that, previous study showed that a combination of non-pharmacological and pharmacological therapy was very essential and effective technique to control fatigue (Hathiramani et al 2020). Furthermore, there is little studies that have been addressed the efficacy of RBE after chemotherapy and the required frequencies for effective fatigue relief result.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Meanwhile, some nurses still believe that cancer related-fatigue is a normal response that experienced by women after chemotherapy, so it does not require intervention (Sanada et al 2017). Other than that, previous study showed that a combination of non-pharmacological and pharmacological therapy was very essential and effective technique to control fatigue (Hathiramani et al 2020). Furthermore, there is little studies that have been addressed the efficacy of RBE after chemotherapy and the required frequencies for effective fatigue relief result.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Artikel terpilih diterbitkan pada 2016-2020, dari 12 artikel yang diulas semuanya berasal dari luar Indonesia; empat artikel berasal dari Amerika Serikat (Carson et al, 2017;Leach et al, 2019;Murley et al, 2019;Pisu et al, 2017), dua dari Amerika Serikat (Hathiramani, 2020;Mijwel et al, 2019), dua dari India (Dhawan et al, 2019;Samuel et al, 2019), dua dari Cina (Huang et al, 2015;Ying & Min, 2019), satu artikel dari Iran (Pasyar et al, 2019), satu artikel dari Korea (Kim et al, 2019). Jumlah responden dalam tinjauan ini adalah 903.…”
Section: Karakteristik Studiunclassified
“…Terapi olahraga yang diberikan pada pasien kanker dalam tinjauan literatur ini bervariasi, mulai dari intervensi tunggal hingga intervensi gabungan. Terapi olahraga yang diberikan meliputi Tai Chi (n=1) (Murley et al, 2019), Aerobik (n=5) (Hathiramani, 2020;Kim et al, 2019;Leach et al, 2019;Mijwel et al, 2019;Samuel et al, 2019), yoga (n=2) (Carson et al, 2017;Pasyar et al, 2019), menari (n=1) (Pisu et al, 2017), Olahraga Baduanjin (n=1) (Ying & Min, 2019), Olahraga Qigong (n=1) (Huang et al, 2015), Olahraga keseimbangan (n=1) (Dhawan et al, 2019). Latihan yang diberikan tatap muka (n=4) (Carson et al, 2017;Huang et al, 2015;Mijwel et al, 2019;Pisu et al, 2017), latihan yang diberikan melalui DVD atau di rumah(n=3) (Dhawan et al, 2019;Hathiramani, 2020;Kim et al, 2019), latihan diberikan tatap muka dan melalui DVD (n=5) (Leach et al, 2019;Murley et al, 2019;Pasyar et al, 2019;Samuel et al, 2019;Ying & Min, 2019).…”
Section: Karakteristik Intervensiunclassified
See 2 more Smart Citations